Co-Processed Excipients in Pharmaceutical Formulation: Advances, Characterization, and Applications - Amar M. Raval,; Prathmesh R Bhavsar,; Foram U Pandya,; Dr. Divyakant Patel, (Asian Journal of Pharmaceutical Research and Development, 2026)
Excipients are indispensable components of pharmaceutical dosage forms, significantly influencing product quality, safety, and performance. Conventional single excipients often fail to meet the growing demands of modern formulation technologies, particularly direct compression and fast dissolving dosage forms. Co-processed excipients have emerged as a novel class of multifunctional excipients developed by physically combining two or more excipients at the sub-particle level without altering their chemical structure. This approach results in synergistic improvement in flowability, compressibility, dilution potential, and disintegration behavior. Various techniques such as spray drying, melt granulation, solvent evaporation, and co-crystallization are employed in the preparation of co-processed excipients. Comprehensive characterization using micromeritic, physicochemical, and solid-state techniques is essential to ensure quality and performance. Co-processed excipients have found extensive applications in direct compression tablets, fast dissolving tablets, immediate-release, and modified-release dosage forms. Despite their advantages, regulatory challenges and limited pharmacopoeial recognition remain key concerns. This review highlights the principles, preparation methods, characterization techniques, applications, commercially available products, regulatory aspects, and future prospects of co-processed excipients.